Predictors of early sexual intercourse on middle adolescents in Medan - Rahmi Lubis; Zahrotur Rusyda Hinduan; Ratna Jatnika; Hendriati Agustiani (Universitas Ahmad Dahlan, 2021)
Early sexual intercourse causes negative consequences for adolescent health. Understanding sexual predictors can be beneficial for the prevention program. This study aims to describe predictors of early sexual intercourse among adolescents. The study participants were twenty sexually experienced respondents aged 15-18 years and received assistance from the Indonesian Family Planning Association (PKBI) in Medan. The study used a qualitative approach using semi-structured interviews as methods. The results show that individual, family, peer, school, and media influence early sexual intercourse. Individually, participants have unstable emotions, negative self-concepts, and unclear future orientation. They are also unable to make rational decisions, lack social responsibility, and often violate the rules. Therefore, sexually, the respondents have positive sexual attitudes, sexually active peers, and high sexual self-efficacy. Especially among male participants, the internet was used to meet sexual partners and watched sexually-laden videos. The participants also have dysfunctional families, friends with behavioral problems, and disengagement with school. Therefore, prevention programs need to strengthen adolescents' positive potential, family function, social support, and healthy media use.